2015
DOI: 10.1039/c5ra20319h
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and hydrolysis of cellulose under subcritical water treatment for the production of total reducing sugars

Abstract: Subcritical water (SCW) treatment has gained enormous attention as an environmentally friendly technique for organic matter and an attractive reaction medium for a variety of applications. In the current work the process parameters were optimized by RSM model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…The slight difference between the spectrums of the sample after SCWE and the control sample provides some evidence of SCWE's ability to break down the chemical structures of cellulose and hemicellulose in the wood matrices of A. malaccensis. Although the changes in FTIR of the sample from SCWE in this work is not apparent, previous studies have demonstrated the effective influence of the SCWE condition on the hydrolysis of the sample's cellulose and hemicellulose to glucose [39,53]. In short, the FTIR analysis showed some changes and partially supports other findings (yield and SEM) from this work.…”
Section: Fourier Transform Infrared Spectroscopy Analysis Of Wood Samplesupporting
confidence: 82%
“…The slight difference between the spectrums of the sample after SCWE and the control sample provides some evidence of SCWE's ability to break down the chemical structures of cellulose and hemicellulose in the wood matrices of A. malaccensis. Although the changes in FTIR of the sample from SCWE in this work is not apparent, previous studies have demonstrated the effective influence of the SCWE condition on the hydrolysis of the sample's cellulose and hemicellulose to glucose [39,53]. In short, the FTIR analysis showed some changes and partially supports other findings (yield and SEM) from this work.…”
Section: Fourier Transform Infrared Spectroscopy Analysis Of Wood Samplesupporting
confidence: 82%
“…On the other hand, higher conversion of sugar into degraded products and the dominancy of pyrolysis reaction explain the dropped of sugar yield observed for both layers with temperature. Sugar decomposed rapidly to degraded products such as 5-HMF and furfural at high temperature and also, may cause some thermally-labile compound degrade after released from the sample matrix [46], [47].…”
Section: Total Sugars (Ws Phase)mentioning
confidence: 99%
“…organic acids, erythrose, glycolaldehyde, furfural, 5-HMF etc. at high temperatures [44], [46]. Moreover, the highest total sugar yields for both layers shared the same maximum temperature peak, 210 °C with those of oligosaccharides.…”
Section: Oligosaccharides and Tri-di- Monosaccharides (Ws Phase)mentioning
confidence: 99%
“…68 The conversion of biomass consists of a set of chemical and biological processes, including separation, conversion of biopolymers into other valuable products, and fermentation reactions. 5,911 Because of the complex structure and strong intra- and intermolecular hydrogen bonding in the biomass, these processes require suitable solvents for the dissolution of its components. 5…”
Section: Introductionmentioning
confidence: 99%